Sorghum Malt Extract as a Growth Medium for Lactic Acid Bacteria Cultures: A Case of Lactobacillus plantarum MNC 21 - Byakika, Stellah; Muzira Mukisa, Ivan; Byenkya Byaruhanga, Yusuf (International Journal of Microbiology, 2020)
Cultivation of lactic acid bacteria cultures is vital for research and commercial production of fermented foods. However, the conventional growth media used are generally costly. Malt extracts from four sorghum varieties (SESO 1, SESO 3, Epuripur, and Eyera) were evaluated as alternative low-cost growth media for Lactobacillus plantarum MNC 21. Saccharified sorghum malt extracts were inoculated with 4 log cfu/mL MNC 21 and incubated at 30°C for 24 h. MRS broth was the reference medium. Microbial counts, pH, titratable acidity (TA), free amino nitrogen (FAN), and total sugars were measured. Maximum microbial counts in the extracts and MRS broth were 9 and 10 log cfu/mL, respectively. Maximum growth rate in the extracts was 0.7–0.9 log cfu/mL/h and 0.8 log cfu/mL/h in MRS broth. (e final pH of the extracts was 3.5–3.6, with an overall increase in TA of 1.2% in Epuripur and 0.2% in other varieties. Final pH and TA of MRS broth were 4.1 and 1.3%, respectively. Total sugars dropped by 95.2% and FAN by 2.1% in MRS broth. In contrast, total sugars and FAN dropped by 5.6–9.1% and 24.9–32.7% respectively, in the extracts. Sorghum malt extracts can be adopted as alternative low-cost growth media for lactic acid bacteria cultures.
Keywords: Sorghum Malt; Growth Medium; Lactic Acid Bacteria Cultures; Lactobacillus plantarum MNC 21